Right Ventricular Function in Acute Respiratory Distress Syndrome: Impact on Outcome, Respiratory Strategy and Use of Veno-Venous Extracorporeal Membrane Oxygenation - Petit, Matthieu; Jullien, Edouard; Vieillard-Baron, Antoine (Frontiers in Physiology, 2022)
Acute respiratory distress syndrome (ARDS) is characterized by protein-rich alveolar edema, reduced lung compliance and severe hypoxemia. Despite some evidence of improvements in mortality over recent decades, ARDS remains a major public health problem with 30% 28-day mortality in recent cohorts. Pulmonary vascular dysfunction is one of the pivot points of the pathophysiology of ARDS, resulting in a certain degree of pulmonary hypertension, higher levels of which are associated with morbidity and mortality. Pulmonary hypertension develops as a result of endothelial dysfunction, pulmonary vascular occlusion, increased vascular tone, extrinsic vessel occlusion, and vascular remodeling. This increase in right ventricular (RV) afterload causes uncoupling between the pulmonary circulation and RV function. Without any contractile reserve, the right ventricle has no adaptive reserve mechanism other than dilatation, which is responsible for left ventricular compression, leading to circulatory failure and worsening of oxygen delivery. This state, also called severe acute cor pulmonale (ACP), is responsible for excess mortality. Strategies designed to protect the pulmonary circulation and the right ventricle in ARDS should be the cornerstones of the care and support of patients with the severest disease, in order to improve prognosis, pending stronger evidence. Acute cor pulmonale is associated with higher driving pressure (≥18 cmH2O), hypercapnia (PaCO2 ≥ 48 mmHg), and hypoxemia (PaO2/FiO2 < 150 mmHg). RV protection should focus on these three preventable factors identified in the last decade. Prone positioning, the setting of positive end-expiratory pressure, and inhaled nitric oxide (INO) can also unload the right ventricle, restore better coupling between the right ventricle and the pulmonary circulation, and correct circulatory failure. When all these strategies are insufficient, extracorporeal membrane oxygenation (ECMO), which improves decarboxylation and oxygenation and enables ultra-protective ventilation by decreasing driving pressure, should be discussed in seeking better control of RV afterload. This review reports the pathophysiology of pulmonary hypertension in ARDS, describes right heart function, and proposes an RV protective approach, ranging from ventilatory settings and prone positioning to INO and selection of patients potentially eligible for veno-venous extracorporeal membrane oxygenation (VV ECMO).